Professional Life Stressors Among Teaching Faculty at Tertiary Level - Mehak Arshad (University of Management and Technology, 2019)
This study was designed to examine the professional life stressors among teaching faculty at tertiary level. The major objectives of the study were the identification of professional life stressors among teachers at tertiary level, finding the differences between life stressors of male and female teachers at tertiary level, and suggesting them some plausible ways to cope with stressors in their daily routine. The current study was descriptive in nature. The population of the study comprised all the teachers teaching at the department of social sciences in 13 public sector universities of Islamabad. Cluster sampling technique was used to draw 200 representatives from the population of four universities. The study concluded that both lifestyle stressors and professional stressors were meaningful for the faculty teaching in the universities of Islamabad. However, professional stress was higher than lifestyle stress among teachers. Career development was the major stressor for teachers teaching at tertiary level. Organizational climate and organizational discipline were also perceived as major sources of stress for teachers at tertiary level. Female teachers of tertiary level had higher levels of stress as compared to male teachers. Relationships at work were least stressful for the faculty teaching in the universities of Islamabad. Based upon the findings of the study, it is recommended that facilities such as equal opportunities of training, quality training and counseling may be provided to teachers by their institutions for their career development and organizations may improve their communication and overall management.